2021
DOI: 10.3802/jgo.2021.32.e84
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of urologic complications requiring urologic procedure in radical hysterectomy and difference between abdominal radical hysterectomy and laparoscopic radical hysterectomy

Abstract: Objective To evaluate the incidence of urologic complications requiring a urologic procedure during the perioperative period and compare the differences between abdominal radical hysterectomy (ARH) and laparoscopic radical hysterectomy (LRH). Methods We identified all Korean women who underwent radical hysterectomy (RH) between January 2006 and December 2019 using the National Health Insurance Service database. Complications requiring surgical intervention-based urologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…A recent study evaluated the incidence of urologic complications requiring urological procedure in radical hysterectomy and the differences in incidence after open and laparoscopic approaches. [ 17 ] The general incidence was 7.4%, with the most common urological procedure being the insertion of double-J catheter 5.18% followed by bladder repair 0.9%,[ 17 ] with no significant difference in urological complications after open or laparoscopic radical hysterectomy, but with significantly higher incidence of bladder repair after the laparoscopic approach. In the present study, the urological complication requiring urological procedures was 7.07% with 3.03% requiring a double-J catheter, 2.02% urethrovesical catheterization (Foley probe), 1.51% surgical management, and 0.5% nephrostomy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study evaluated the incidence of urologic complications requiring urological procedure in radical hysterectomy and the differences in incidence after open and laparoscopic approaches. [ 17 ] The general incidence was 7.4%, with the most common urological procedure being the insertion of double-J catheter 5.18% followed by bladder repair 0.9%,[ 17 ] with no significant difference in urological complications after open or laparoscopic radical hysterectomy, but with significantly higher incidence of bladder repair after the laparoscopic approach. In the present study, the urological complication requiring urological procedures was 7.07% with 3.03% requiring a double-J catheter, 2.02% urethrovesical catheterization (Foley probe), 1.51% surgical management, and 0.5% nephrostomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, when considering urologic complications, clear differences between the open and minimally invasive approaches have not been identified [62]. The LACC trial brought about a radical change in cervical cancer surgery by leading to a dramatic shift to the surgical open technique [35].…”
Section: Discussionmentioning
confidence: 99%
“…-Many of the studies we found were retrospective, which could reduce the level of evidence; -We excluded all non-English studies, potentially introducing a bias to our findings; -Stratification based on the cervical cancer stage was not possible, since few studies provided this information, even if cervical cancer stage is one of the most relevant risk factors for surgical urologic complications [35]; -…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in comparison to total hysterectomy, radical hysterectomy has a higher risk of surgery related complications, such as urinary, nerve and vascular injury(Obermair et al 2020 ; Kim et al 2021 ; Plante et al 2023 ). The incidence of postoperative urinary incontinence and urinary retention is 11.0% and 9.9%, respectively, in patients receiving radical hysterectomy, compared to 4.7% and 0.6%, respectively, in patients undergoing total hysterectomy(Plante et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%